Use of public data to describe COVID-19 contact tracing in Hubei Province and non-Hubei provinces in China between 20 January and 29 February 2020 - Dirlikov, Emilio; Zhou, Suizan; Han, Lifeng; Li, Zhijun; Hao, Ling; Millman, Alexander; Marston, Barbara (Western Pacific Surveillance and Response, 2021)
Objective: Contact tracing has been used in China and several other countries in the WHO Western Pacific Region as part of the COVID-19 response. We describe COVID-19 cases and the number of contacts traced and quarantined per case as part of COVID-19 emergency public health response activities in China. Methods: We abstracted publicly available, online aggregated data published in daily COVID-19 situational reports by China’s National Health Commission and provincial health commissions between 20 January and 29 February 2020. The number of new contacts traced by report date was computed as the difference between total contacts traced in consecutive reports. A proxy for the number of contacts traced per case was computed as the number of new contacts traced divided by the number of new cases. Results: During the study period, China reported 80 968 new COVID-19 cases and 659 899 contacts. In Hubei Province, there were 67 608 cases and 264 878 contacts, representing 83% and 40% of the total, respectively. Non-Hubei provinces reported tracing 1.5 times more contacts than Hubei Province; the weekly number of contacts traced per case was also higher in non-Hubei provinces than in Hubei Province and increased from 17.2 in epidemiological week 4 to 115.7 in epidemiological week 9. Discussion: More contacts per case were reported from areas and periods with lower COVID-19 case counts. With other non-pharmaceutical interventions used in China, contact tracing and quarantining large numbers of potentially infected contacts probably contributed to reducing SARS-CoV-2 transmission.